Methionine-Mediated Regulation of Intestinal Lipid Transportation Induced by High-Fat Diet in Rice Field Eel (Monopterus Albus) - Yajun Hu; Junzhi Zhang; Minglang Cai; Wuying Chu; Yi Hu (Aquaculture Nutrition)
An eight-week feeding trial explored the mechanism that supplemented methionine (0 g/kg, 4 g/kg, 8 g/kg, and 12 g/kg) in a high-fat diet (120 g/kg fat) on intestinal lipid transportation and gut microbiota of M. Albus (initial weight 25.03±0.13 g) based on the diet (60 g/kg fat), named as Con, HFD+M0, HFD+M4, HFD+M8, and HFD+M12, respectively. Compared with Con, gastric amylase, lipase, trypsin (P<0.05), and intestinal lipase, amylase, trypsin, Na+/K+ -Adenosinetriphosphatase, depth of gastric fovea, and the number of intestinal villus goblet cells of HFD+M0 were markedly declined (P<0.05), while intestinal high-density lipoprotein-cholesterol, very low-density lipoprotein-cholesterol and microsomal triglyceride transfer protein of HFD+M0 were markedly enhanced (P<0.05); compared with HFD+M0, gastric lipase, amylase, trypsin, and intestinal lipase, trypsin, Na+/K+ -Adenosinetriphosphatase, microsomal triglyceride transfer protein, very low-density lipoprotein-cholesterol, and apolipoprotein -A, the height of intestinal villus and the number of intestinal villus goblet cells of HFD+M8 were remarkably enhanced (P<0.05). Compared with Con, intestinal occ, cl12, cl15, zo-1, zo-2 of HFD + M0 were markedly down-regulated (P <0.05), while intestinal vldlr, npc1l1, cd36, fatp1, fatp2, fatp6, fatp7, apo, apoa, apob, apof, apoo, mct1, mct2, mct4, mct7, mct12, lpl, mttp, moat2, dgat2 of HFD M0 were remarkably upregulated (P<0.05); compared with HFD+M0, intestinal gcn2 and eif2α of HFD+M8 were remarkably downregulated (P<0.05), intestinal occ, cl12, cl15, zo-1, zo-2, hdlbp, ldlrap, vldlr, cd36, fatp1, fatp2, fatp6, apo, apoa, apob, apof, apoo, mct1, mct2, mct8, mct12, lpl, mttp, moat2, and dgat2 were remarkably upregulated (P<0.05). Compared with Con, the diversity of gut microbiota of HFD+M0 was significantly declined (P<0.05), while the diversity of gut microbiota in HFD+M8 was significantly higher than that in HFD+M0 (P<0.05). In conclusion, a high-fat methionine deficiency diet destroyed the intestinal barrier, reduced the capacity of intestinal digestion and absorption, and disrupted the balance of gut microbiota; supplemented methionine promoted the digestion and absorption of lipids, and also improved the balance of gut microbiota.